PENGARUH JOB DEMANDS DAN PSYCHOLOGICAL CAPITAL TERHADAP BURNT OUT DENGAN EFEK MODERASI SUPERVISORY SUPPORT - Endang Retno; Sri Subiyandani (Jurnal Riset Bisnis Indonesia, 2016)
And the statistical The increasement of diverse statistical data requests at the same time and with thesupport of limited human resources lead to a high volume of work in the BPS. Those conditions leadto work overload that induce the job burnout. Some of the factors generate the workload pressureare the differences of operational and procedure standard between local goverments and the BPSadministration descriptive create so many differences in product administration and procedures,statistical data officer are dealing with the data which are coverage in a very large scope area,dealing with the uncooperative respondents, and the most severe problem is the deadline ofthe result. This explanatory study aims to examine how to mute the job burnout in the context ofsupervisory support. The population in this study are 112 responden come from BPS Cilacap,Kebumen regency, Magelang regency, Tegal regency, Klaten regency, Kudus and Semarang, usingsampling techniques incidental then the data were analyzed by partial least squares analysis. Theresults of data analysis can be concluded that supervisory support will affect the willingness of humanresourcesto encounter job demands. No significant effect psychological capital on job burnout.Jjobdemands has significant correlation with job burnout. Supervisory support did not moderate therelationship of psychological capital on job burnout. Supervisory support moderate the relationshipof psychological capital on job burnout.Keywords: supervisory support, job demands, Psychological capital, job burnout.